Shame and guilt activations: Associations and sociodemographic differences among ploysubstance abusers - Abbasi, Najam ul Hasan; Iqbal, Mujahid; Yan, Yu; Mubarik, Sumaira; Nadeem, Muhammad; Turan, Mehmet Behzat; Younas, Romana (Frontiers in Psychiatry, 2022)
Objectives Shame and guilt in polysubstance abusers are still understudied despite their significance in substance use disorders (SUD). The goal of the current study is to develop a better understanding of how shame and guilt interact among polysubstance abusers who are receiving residential treatment. Methods The sample of two hundred four males with SUD admitted to five rehabilitation centers from two cities in Pakistan participated in this study. For comparison, 215 age-matched healthy individuals were recruited (control). All participants reported their scores on the state shame and guilt scale (SSGS) and demographic form. A cross-sectional study design was adopted. Results The group with SUD reported greater activations on SGSS (r = 0.79, p < 0.001) as compared to healthy (control) individuals (r = 0.48, p < 0.001). Further, multivariate analysis indicated that people with SUD who were of older age, unemployed, living in a nuclear family system, with a higher level of education, and low income, experienced higher levels of shame and guilt. Multinomial logistic regression analysis revealed that people with SUD in the age group 41–60 years (OR 5.2, 95%CI 2.4–6.8), unemployed (OR 4.4, 95%CI 3.2–4.7), nuclear family system (OR 5.9, 95%CI 4.5–6.4) and low monthly income group (OR 5.4, 95%CI 3.5–5.8) had a significantly high risk of shame and guilt than the control group. Conclusion Findings of the current study indicate an association between shame and guilt activation and SUD. These results suggest that polysubstance users may benefit from therapeutic interventions to avoid a generalization of shame and guilt toward their substance use. Reducing shame and guilt should be considered a priority in treating adults with multiple SUD.